An Uncommon Hypervalent Fluorooxosilicophosphate. Issue 23 (28th November 2019) - Ding, Qingran; Zhao, Sangen; Xiao, Han; Li, Yanqiang; Liu, Shuai; Li, Lina; Li, Chunsen; Wang, Yusong; Hong, Maochun; Luo, Junhua
Abstract: The species diversity of silicon (including traditional tetrahedral coordinated silicon and hypervalent penta‐ and hexa‐coordinate silicon) gives rise to the structural richness and diverse properties of silicates. Among these silicon species, hypervalent silicon is very rare, not to mention almost unexplored mixed‐anion hypervalent fluoroxosilicate species. In this work, we successfully obtained a mixed‐anion fluorooxosilicophosphate Na4Si2PO4F9 consisting of two uncommon hypervalent fluoroxosilicate species, namely, trans ‐SiO2F4 species and SiOF5 species. To the best of our knowledge, such hypervalent silicon species are reported for the first time in inorganic compounds. Remarkably, the coexistence of two distinct hypervalent fluoroxosilicate species in one compound is somewhat conflicted with Pauling's parsimony rule, but it indeed achieves an unlikely connection by PO4 and our phonon dispersion calculation confirms the structure stability of Na4 Si2 PO4 F9 . Temperature‐dependent conductivity measurements show that Na4 Si2 PO4 F9 is a promising solid ionic conductor with a high conductivity of 4.0×10 −5 S⋅cm −1 at 700 K and a low active energy of about 53.1 KJ⋅mol −1 . This work will enrich the structure chemistry of silicates and may provide a new platform for solid ionic batteries. Abstract : Hyperactive : A fluorooxosilicophosphate Na4 Si2 PO4 F9 consists of two uncommon hypervalent fluorooxosilicate species ( trans ‐SiO2 F4 and SiOF5 ) and exhibits a high conductivity of 4.0×10 −5 S⋅cm −1 at 700 K and a low active energy of about 53.1 KJ⋅mol −1 .